2022
DOI: 10.3389/fimmu.2022.851765
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells Profiles In The Peripheral Blood Of Patients With Moderate To Severe COVID-19 And Healthy Subjects With and Without Vaccination With The Pfizer-BioNTech mRNA Vaccine

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus disease 2019 (COVID-19), has caused a global crisis. Patients with COVID-19 present with a range of clinical manifestations, from no symptoms to severe illness. However, little is known about the profiles of immune cells required to protect against SARS-CoV-2. This study was performed to determine the immune cells profiles in the peripheral blood of COVID-19 patients with moderate to severe disease (n=52), and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In line with this, BNT162b2 mRNA booster vaccination induced higher frequency of CD14 + CD16 + inflammatory monocytes ( 33 ). This non-classical monocyte population was decreased in SARS-CoV-2-infected patients compared to those in the healthy controls or vaccinated individuals, suggesting that they might contribute to viral control ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, BNT162b2 mRNA booster vaccination induced higher frequency of CD14 + CD16 + inflammatory monocytes ( 33 ). This non-classical monocyte population was decreased in SARS-CoV-2-infected patients compared to those in the healthy controls or vaccinated individuals, suggesting that they might contribute to viral control ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 Interestingly, we found higher monocytes in vaccinated patients at discharge, which underlies the mechanism of higher monocyte activation following vaccination in COVID-19. 29 Studies have also shown that disease severity scores and the degree of the rise of inflammatory markers are associated with a higher risk of mortality. 30 The effectiveness of vaccination in reducing the severity of COVID-19 infection, including the need for hospitalization and death from COVID-19, has now been well-established by numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Interestingly, we found higher monocytes in vaccinated patients at discharge, which underlies the mechanism of higher monocyte activation following vaccination in COVID‐19. 29 Studies have also shown that disease severity scores and the degree of the rise of inflammatory markers are associated with a higher risk of mortality. 30 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that COVID-19 can induce significant decreases in several components of the cellular immune response, including cytokines, complements, and immune cells ( 303 , 324 , 325 ). Recent research showed marked reductions in counts and percentages of total lymphocytes, total T cells, CD4 + T cells, CD8 + T cells, B cells, and natural killer cells (NK) without changes in the typical TCD4:TCD8 ratio of approximately 1:1 in healthy subjects whether vaccinated or unvaccinated, who are COVID-19 survivors ( 324 ) ( Figure 1 ). Substantial dysregulations in CD8 + T cells expressing degranulation markers have been reported after SARS-CoV-2 infection ( 24 ).…”
Section: Immune Response During Long Covidmentioning
confidence: 99%